Determination of the minimal erythema dose for ultraviolet A1 radiation. (1st July 2017) - Gambichler, T.; Majert, J.; Pljakic, A.; Rooms, I.; Wolf, P.
Summary: Background: There is limited knowledge of the potential of ultraviolet A1 (UVA1) radiation to induce erythema. Objectives: To investigate the minimal erythema dose (MED) for UVA1 in a German and Austrian population and to determine UVA1 dose–response curves for erythema and pigmentation. Methods: We determined the UVA1‐MED in 59 participants using a geometric increase in the dose. Visual readings of erythema and pigmentation were performed at 10 min, 2 h and 24 h after the UVA1 irradiation. Colorimetric measurements were taken to determine erythema (a* value) and pigmentation (L* value) objectively. Results: More than 30% (18 of 59) of the participants had a high‐dose UVA1‐MED (> 70–130 J cm −2 ); 56% (33) had no detectable UVA1‐MED after 24 h and eight (14%) had a medium‐dose UVA1‐MED (20–70 J cm −2 ). We observed a stepwise decrease of the a* value measured at the UVA1‐MED skin site from 10 min to 2 h and 24 h ( P < 0·001). In contrast, there was a stepwise increase of the L* value measured at the UVA1‐MED skin site from 10 min to 2 h and 24 h ( P < 0·001). Conclusions: Most participants had no measurable UVA1‐MED even after commencing high doses such as 130 J cm −2 . Only a minority of participants (14%) may develop UVA1‐induced erythema in the low‐ and medium‐dose region. Hence, it appears to be safe to start UVA1 phototherapy with 20 J cm −2 of UVA1 and continue with subsequent daily dose increments of 10 J cm −2, up to the desired maximum dose.